2021
DOI: 10.1152/ajpheart.00366.2021
|View full text |Cite
|
Sign up to set email alerts
|

Hypernatremia and intercalated disc edema synergistically exacerbate long-QT syndrome type 3 phenotype

Abstract: Background: Cardiac voltage-gated sodium channel gain-of-function prolongs repolarization in the Long-QT Syndrome Type 3 (LQT3). Previous studies suggest that narrowing the perinexus within the intercalated disc, leading to rapid sodium depletion, attenuates LQT3-associated action potential duration (APD) prolongation. However, it remains unknown whether extracellular sodium concentration modulates APD prolongation during sodium channel gain-of-function. We hypothesized that elevated extracellular sodium conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Along these lines, other inflammatory proteins such as vascular endothelial growth factor also disrupt gap junctions resulting in conduction slowing predisposing normal hearts to arrhythmias (137). Langendorff-perfused guinea pig heart preparations have also been used to investigate the effects of perinexal width variation on arrhythmia susceptibility and how this may be modulated by extracellular sodium and calcium concentrations experimentally (138)(139)(140). It is therefore possible that the inflammatory secretome of EAT may exert proarrhythmic effects by modulating both gap junction and ephaptic coupling.…”
Section: Gap Junction Modulationmentioning
confidence: 99%
“…Along these lines, other inflammatory proteins such as vascular endothelial growth factor also disrupt gap junctions resulting in conduction slowing predisposing normal hearts to arrhythmias (137). Langendorff-perfused guinea pig heart preparations have also been used to investigate the effects of perinexal width variation on arrhythmia susceptibility and how this may be modulated by extracellular sodium and calcium concentrations experimentally (138)(139)(140). It is therefore possible that the inflammatory secretome of EAT may exert proarrhythmic effects by modulating both gap junction and ephaptic coupling.…”
Section: Gap Junction Modulationmentioning
confidence: 99%
“…In terms of species used, the majority of these studies (∼67%) used rodents, with approximately equal distribution between mice ( 23 33 ) and rats ( 34 42 ). Guinea pig ( 43 45 ) and porcine hearts ( 46 48 ) were each used in ∼10% of studies, followed by a small number of reports in rabbit ( 49 ), zebrafish ( 50 ), quail ( 51 ), and canine ( 52 ) hearts. Overall, there was good reporting of sex, age, and strain, yet only ∼30% of studies evaluated both male and female animals, whereas ∼40% exclusively reported data from male animals.…”
Section: Evaluation Of Current Literaturementioning
confidence: 99%
“…In terms of disease models, genetically modified mice ( 23 , 26 , 28 33 ) or specific rat strains (e.g., spontaneously hypertensive rat) ( 34 , 35 , 40 ) were most commonly assessed (∼37% of studies), and myocardial infarction, ischemia, or hypoxia were evaluated in ∼27% of studies ( 25 , 31 , 35 , 38 , 42 , 44 , 45 , 47 ). Around 16% of investigations used pharmacological modulation ( 24 , 43 , 49 , 50 , 52 ). A small number of studies investigated environmental effects [including herbicide ( 36 ), vaping ( 27 ), and alcohol ( 51 )], aging and development ( 25 , 28 , 41 ), nonischemic heart failure ( 39 ), and the remaining studies performed electrophysiological assessments in nondiseased hearts ( 37 , 46 , 48 ).…”
Section: Evaluation Of Current Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This lack of information can affect the candidacy of an animal model to predict human cardiovascular behavior as it relates to normal cardiac physiology, pathophysiology, or drug safety and efficacy testing. Guinea pigs have been used as a translational model for preclinical assessment of cardiac electrophysiology ( Greer-Short et al, 2017 ; Cooper et al, 2021 ; Wu et al, 2021 ) and arrhythmia susceptibility ( Woulfe et al, 2018 ), due in part to similarities in ionic currents, cardiac action potential shape, and the influence of excitation-contraction coupling ( Luo and Rudy, 1994 ; Bers, 2000 ; Edwards and Louch, 2017 ). Indeed, a validation study reported that guinea pig models have a high level of specificity and sensitivity in predicting clinical outcomes to reference compounds known to widen the QRS complex, lengthen QT duration, or precipitate heart block ( Guo et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%